Perception of Medical Students Regarding TU-IOM MBBS Curriculum and Teaching Learning Methods in Nepal - Gautam, N.; Dhungana, R.; Gyawali, S.; Dhakal, S.; Pradhan, P. M. S. (Kathmandu University Medical Journal, 2022)
Background The present Bachelor of Medicine and Bachelor of Surgery (MBBS) curriculum under Tribhuvan University - Institute of Medicine (TU-IOM) was last revised twelve-years back. Though the curriculum was built upon internationally approved recommendations on curriculum design, it is ineffectively practiced in most medical schools of Nepal with major focus on didactic teaching-learning. The curriculum, hence, needs effective implementation and revision. Objective To identify the strengths, weaknesses, and areas of improvement in the medical curriculum through student-based feedback and outline the possibility of incorporating newer evidence-based teaching-learning methodologies in Nepal. Method This is a descriptive and cross-sectional study. With appropriate ethical approval, a questionnaire was developed and disseminated virtually to all medical students of Nepal under TU from MBBS fourth year onwards. The questionnaire comprised of Likert and close-ended questions. The data analysis was followed after receiving the filled questionnaire through Google forms. Result A total of 337 respondents participated in the study. The most effectively implemented components out of the SPICES model were Integrated learning (I) and Community-based learning (C), with 73.89% and 68.84% responses. There were 94.7% (319) students who favored the incorporation of research in the core curriculum. Only 34.2% (115) students found PowerPoint lectures, the most utilized form of teaching-learning in Nepal, as engaging. The respondents (84.6%) showed a high degree of readiness to incorporate newer evidence-based teaching-learning tools such as flipped learning, blended learning, and peer-to-peer learning. Conclusion This study shows that effective interventions must be rethought on various aspects of the curriculum, taking students’ feedback on the table while considering curricular revision.